1980
DOI: 10.1161/01.cir.61.2.441
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cardiomyopathy in infants of diabetic mothers.

Abstract: SUMMARY A transient form of hypertrophic cardiomyopathy has been previously described in infants of diabetic mothers (IDMs). The purpose of this study was to determine the incidence, natural history and pathologic features of this cardiomyopathy in symptomatic and asymptomatic IDMs.We studied 47 IDMs for evidence of cardiomyopathy. Among 24 symptomatic IDMs, five had marked septal hypertrophy with echocardiographic features suggesting left ventricular outflow obstruction and five had hypertrophy of the right v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
1
4

Year Published

1980
1980
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(80 citation statements)
references
References 41 publications
5
68
1
4
Order By: Relevance
“…In FDM, serum glucose and insulin levels were significantly greater than control values (Table 1). This finding is consistent with previous observations in human and animal FDM (3,8). In the present study, body weight in FDM was not significantly greater than control ( Table 1).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In FDM, serum glucose and insulin levels were significantly greater than control values (Table 1). This finding is consistent with previous observations in human and animal FDM (3,8). In the present study, body weight in FDM was not significantly greater than control ( Table 1).…”
Section: Discussionsupporting
confidence: 94%
“…In newborns of diabetic mothers, cardiac abnormalities such as hypertrophic cardiomyopathy, left ventricular outflow obstruction, and congestive heart failure may occur (8). Hyperinsulinemia, hyperglycemia, and other alterations in carbohydrate, lipid, and protein metabolism occur in the fetus of the diabetic mother (3,12,22,23).…”
mentioning
confidence: 99%
“…The severity of the situation is related to the control of diabetes 29 . Microscopic alterations of the hypertrophic myocardium of the infants of diabetic mothers include, in addition to hyperplasia and hypertrophy, a disorganization of the normal pattern of the myofibrils, similar to that found in the cardiomyopathy of the adult 30 .…”
Section: Discussionsupporting
confidence: 56%
“…[Diabetologia (2002) rosomia is related to an increased risk for "unexplained" death in utero and shoulder dystocia during labour, the latter being related to asphyxia, clavicle fracture and/or Erbs palsy [1,2,3]. During the neonatal period macrosomic infants are at increased risk for hypoglycaemia, infant respiratory distress syndrome (IRDS), hyperbilirubinaemia and hypertrophic cardiomyopathy [4,5,6]. A number of long-term population studies have shown that macrosomic newborns of women with diabetes have a higher risk to develop obesity and Type II (non-insulin-dependent) diabetes mellitus at a young age [7,8,9].…”
mentioning
confidence: 99%